2018
DOI: 10.12659/msm.909353
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Glomerular Cell Senescence in Experimental Lupus Nephritis

Abstract: BackgroundThe aim of this study was to determine whether senescence in renal glomeruli is involved in lupus nephritis (LN); the expression of senescence-associated β-galactosidase (SA-β-Gal) and its association with glomerular lesions were investigated in a mouse model of LN.Material/MethodsEighteen MRL/lpr mice with severe proteinuria were randomly divided into 2 equal groups and intraperitoneally injected with dexamethasone (DEX) or saline; 4 age-matched mice with mild proteinuria served as controls. Serum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
(29 reference statements)
3
21
0
Order By: Relevance
“…Renal diseases such as IgA nephropathy and lupus nephritis associate with increased senescent cell burden (Liu et al, 2012; Yang et al, 2018), but diabetes mellitus is the most studied disease regarding cellular senescence in the kidney.…”
Section: Cellular Senescence In the Aging And Injured Kidneymentioning
confidence: 99%
“…Renal diseases such as IgA nephropathy and lupus nephritis associate with increased senescent cell burden (Liu et al, 2012; Yang et al, 2018), but diabetes mellitus is the most studied disease regarding cellular senescence in the kidney.…”
Section: Cellular Senescence In the Aging And Injured Kidneymentioning
confidence: 99%
“…It hydrolyzes β-galactosides to monosaccharides and the enzyme is active even at acidic pH (6.0). SA-β-gal activity has been widely used as a reliable marker of cellular senescence in brain (20)(21)(22) and other organs (23,24). In the present study, using an advanced blast simulator (ABS) to expose animals to single and tightly coupled repeated blasts, we have carried out postmortem evaluation of SA-β-gal activity in different anatomical regions of the brain at various time points up to 1 year post-blast exposures to determine whether blast exposure accelerate cellular senescence, an indicator of aging processes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, evidence of senescence in the kidney can occur without evidence of telomere shortening [ 64 ]. Very recently, data shows biomarkers of cellular senescence in murine and human lupus including upregulation of SABG and p16 ink4a [ 65 ••, 66 ]. These studies have shown a potential role for wnt9a in renal cellular senescence and fibrosis [ 65 ••].…”
Section: Cellular Senescence In Organ Systems With Lupusmentioning
confidence: 99%